Theoretical and Practical Approaches in Watershed Management Across Different Environmental Contexts - Demetrio Antonio Zema; Manuel Esteban Lucas-Borja (Resources)
A watershed is defined as ‘a topographically delineated area that is drained by a stream system’ [...]